Essays on the role of expectation dynamics, social influence and technology diffusion on efficiency, growth and inequality - Terranova, Roberta (Universität Bielefeld, 2021)
Terranova R. Essays on the role of expectation dynamics, social influence and technology diffusion on efficiency, growth and inequality . Bielefeld: Universität Bielefeld; 2021.